Công văn phối hợp giám sát việc thực hiện chính sách, pháp luật về công tác quy hoạch (Số: 47/KTNN-TH) (2022)
Toàn văn Công văn phối hợp giám sát việc thực hiện chính sách, pháp luật về công tác quy hoạch (Số: 47/KTNN-TH)